Internalisasi Kearifan Lokal di Kampung Buddha dalam Mitigasi COVID-19: The Internalization of Local Wisdom in the Buddhist Kampong for Mitigating COVID-19 - Muhammad Hanif (Society, 2023)
Communities across the globe are grappling with the COVID-19 pandemic by leveraging their local wisdom, and the Buddhist Kampong in Sodong Hamlet is no exception. Buddhist Kampong has experienced minimal COVID-19 exposure, demonstrating a proficient response to the pandemic. However, this success story remains largely unknown to various stakeholders, necessitating comprehensive research to delineate and elucidate the intrinsic value of local wisdom and its assimilation process. Using an ethnographic approach, this two-year research project was carried out in Sodong Hamlet, Gelangkulon, Sampung Ponorogo, East Java, Indonesia. Primary and secondary sources were tapped, with research informants identified as traditional, religious, and community leaders. Data collection encompassed interviews, observations, and document recordings, all analyzed using an interactive model. The findings revealed a distinct value system within the Buddhist Kampong, shaping their approach to COVID-19 mitigation. This value system revolves around the principles of Memayu Hayuning Kulawarga, Memayu Hayuning Sasama, and Memayu Hayuning Bawana, influencing the community’s engagement in check-in rituals, care for sasomo and cooperation, and the restoration of padasan and diyang. The figures embodying this local wisdom guide community members in internalizing customs, religion, and parental teachings. The internalization process unfolds through exemplary habituation, socialization, and the cultivation of moral motivation, empowering citizens to navigate the challenges posed by the COVID-19 pandemic effectively.